2013
DOI: 10.4103/0974-777x.122010
|View full text |Cite
|
Sign up to set email alerts
|

Infection control and practice of standard precautions among healthcare workers in northern Nigeria

Abstract: Background:Healthcare-associated infections (HAIs) have been reported to be a serious problem in the healthcare services as they are common causes of illness and mortality among hospitalized patients including healthcare workers (HCWs). Compliance with these standard precautions has been shown to reduce the risk of exposure to blood and body fluids.Aims:This study therefore assesses the level of knowledge and compliance with standard precautions by the various cadre of HCWs and the factors influencing complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 31 publications
12
66
3
2
Order By: Relevance
“…24,25 A majority of present respondents understood the role of isolation as an integral part of the management of EVD which was similar to a study in Liberia but contrasted from others Sierra Leone and England. 10,18,20 This knowledge is vital especially in young inexperienced HCW as it is a necessary initial step in preventing further transmission of the virus in the community.…”
Section: Discussionmentioning
confidence: 58%
“…24,25 A majority of present respondents understood the role of isolation as an integral part of the management of EVD which was similar to a study in Liberia but contrasted from others Sierra Leone and England. 10,18,20 This knowledge is vital especially in young inexperienced HCW as it is a necessary initial step in preventing further transmission of the virus in the community.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, study by Amoran and Onwube (2013) [33] revealed that majority of respondents reported that non availability of the equipments was a major reason for noncompliance to standard precautions. However, Oliveria et al…”
Section: Discussionmentioning
confidence: 99%
“…Although they were illiterate and usually exposed to human blood and fluids but they were significantly have shown the knowledge about positive practices for protection. This is supported by study in Nigeria among health care workers where exposure to blood and body fluids predicted the practices of standard precautions at health facilities [22]. Village midwives with age more than 35 years were significantly had general knowledge, attitude and knowledge about practices regarding Hepatitis B virus.…”
Section: Resultsmentioning
confidence: 57%